Molecular and prognostic correlates of cytogenetic abnormalities in chronic myelomonocytic leukemia: a Mayo Clinic‐French Consortium Study. Issue 12 (26th September 2014) - Wassie, Emnet A.; Itzykson, Raphael; Lasho, Terra L.; Kosmider, Olivier; Finke, Christy M.; Hanson, Curtis A.; Ketterling, Rhett P.; Solary, Eric; Tefferi, Ayalew; Patnaik, Mrinal M.
<x xml:space="preserve">Abstract</x> Four hundred and nine patients with chronic myelomonocytic leukemia (CMML) were included in the international collaborative study (268 (66%) and 141 (34%) from Mayo clinic and French consortium respectively). Thirty percent displayed an abnormal karyotype, including; 72% sole, 16% two, and 11% complex abnormalities. The most common abnormalities included; +8 (23%), ‐Y (20%), ‐7/7q‐(14%), 20q‐ (8%), +21 (8%), and der(3q) (8%). Patients with an abnormal karyotype were more likely to be elderly (P = 0.03), be anemic (P = 0.0009), have leukocytosis (P = 0.02) with neutrophilia (P = 0.03), demonstrate increased circulating immature myeloid cells (P = 0.0003), peripheral blood blasts (P < 0.0001), and bone marrow blasts (P < 0.0001). ASXL1 (P = 0.04) and SF3B1 (P = 0.03) mutations clustered with an abnormal karyotype, whereas SRSF2 (P = 0.02) mutations occurred more commonly with a normal karyotype. A step‐wise survival analysis resulted in three distinct cytogenetic risk categories: high (complex and monosomal karyotypes), intermediate (all abnormalities not in the high or low risk groups) and low [normal, sole ‐Y and sole der (3q)] with median survivals of 3 [hazard ratio (HR) = 8.1, 95% confidence interval (CI) = 4.6–14.2], 20 (HR = 1.7, 95% CI = 1.2–2.3) and 41 months, respectively. In multivariable analysis, this particular cytogenetic risk stratification remained significant in the context of the Molecular Mayo Model (P < 0.0001), MD Anderson prognostic model (P < 0.0001), the GFM CMML model (P < 0.0001) and was effective in predicting leukemic transformation (P = 0.004). Am. J. Hematol. 89:1111–1115, 2014. © 2014 Wiley Periodicals, Inc.